The Current and Evolving Role of Immunotherapy in Metastatic Colorectal Cancer - Silva, Virgilio S.; Riechelmann, Rachel P.; Mello, Celso A.; Felismino, Tiago; Taboada, Rodrigo (Current Cancer Drug Targets, 2022)
Immunotherapy can be considered a therapeutic revolution in oncology, with great impact on many tumor types, such as melanoma and non-small cell lung cancer. However, in metastatic colorectal cancer, the benefits in terms of prolonged tumor control and high response rate are limited to the rare subgroup of tumors with high mutation burden - mostly tumors that harbor microsatellite instability (MSI) or a deficient mismatch repair system (dMMR), or tumor microsatellite stability and damaging mutations in the exonuclease domains of POLE or POLD. The KEYNOTE-028 uncontrolled phase II trial demonstrated an impressive antitumor activity of pembrolizumab in patients with treatmentrefractory Lynch-associated tumors, including colorectal cancer. Nivolumab with or without ipilimumab confirmed the efficacy of immune checkpoint inhibitors in patients with previously treated dMMR / MSI metastatic colorectal cancer. The recent KEYNOTE-177 phase III trial demonstrated that pembrolizumab significantly reduced the relative risk of disease progression or death and improved progression-free survival in patients with treatment-naive dMMR / MSI metastatic colorectal cancer in comparison with first-line chemotherapy with or without biologics. Unfortunately, current pharmacological strategies with immunotherapy have not been successful for most patients with microsatellite stable metastatic colorectal cancer. In this review, we critically appraise the applicability of immune checkpoint inhibitors in dMMR/MSI metastatic colorectal cancer. We also discuss the recent negative trials of immunotherapy combinations in microsatellite stable tumors and more mature immunotherapy ongoing studies in the field of advanced colorectal cancer.
Keywords: microsatellite instability